(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Making connections and building relationships online are made easier by the social networking sites in the present times. In this paper, alleged sexual assault of a minor girl by different perpetrators whom she met on social networking sites is presented. On analysis of the sequence of events and nature of the offence, the girl seemed to be following the same modus operandii.e. she gets in a party with Facebook friends whom she had never met before and then charges them with sexual assault later and agrees to a financial settlement. On the other hand, POCSO or The Protection of Children from Sexual Offences Act (POCSO Act) 2012 is anAct to protect children against offences like sexual abuse, sexual harassment and pornography.Under POCSO, there is a presumption that a person who is prosecuted for an offence has actually committed the offence, unless the contrary is proved. This paper has been presented to enable the public to take proper care of underage children’s exposure to the social networking sites.